A comparison of the high-temperature oxidation behaviour of conventional wrought and laser beam melted Inconel 625. (March 2020) - Ramenatte, Nicolas; Vernouillet, Annabelle; Mathieu, Stéphane; Vande Put, Aurélie; Vilasi, Michel; Monceau, Daniel
Highlights: LBM Inconel 625 exhibits microstructure with Nb and Mo segregations at cell walls. LBM and CM Inconel 625 showed similar oxidation resistance at 900 °C. CM Inconel 625 evidenced larger oxidation resistance than LBM ones at 1050 °C. The formation of Nb1.5 Cr0.5 O4 explains the difference observed at 1050 °C. Nb distribution is responsible of the high oxidation rate noticed at 1050 °C. Abstract: The microstructure and oxidation resistance of Laser Beam Melted (LBM) and Conventionally Manufactured (CM) Inconel 625 alloys were studied at 900 °C and 1050 °C. The microstructure of the LBM samples was cellular, with Nb and Mo segregations located at the cell walls. At 900 °C, the oxidation rate was similar for both materials but was clearly higher for the LBM material at 1050 °C. This high oxidation rate induced poor oxide scale compactness, void formation in the subsurface region and the formation of a high amount of Nb1.5 Cr0.5 O4 at the alloy-oxide interface.